HABITAT DAN PERILAKU KANGKARENG PERUT-PUTIH (Anthracoceros albirostris convexus Temm. 1832) DI RESORT ROWOBENDO TN ALAS PURWO - Tarigan, Salvionita BR; Hernowo, Jarwadi Budi (Media Konservasi, 2016)
Oriental pied hornbill (Anthracoceros albirostris) is one of hornbill spesies (Bucerotidae) that protected in Indonesia based on Goverment Regulation No. 7/1999. The habitat of oriental pied hornbillin Resort Rowobendo Alas Purwo National Park (APNP) are natural forest and mixed forest plantation. The characteristic of the bird feeding site is a fruiting tree with a thick meat with the shaped is an oval, thin rind, soft, and contain more water and has sweet taste. The characteristic for the birdresting site is a tree with dense leaf, horizontal withstrong enough branch to withstand oriental pied hornbill. The tree height is about 10-26 m and the diameters  about 29-71 cm. The nesting site characteristic the bird is a tree with diameters about ≥ 50 cm and the height is about ≥10 m. The tree has a hole, main branch that is large and fairly flat with the height of the nest from the ground level of 12-30 m. Behavior of oriental pied hornbill observed are eating, resting, calling, flying and nesting. Keywords: APNP, behavior, habitat, oriental pied hornbill